2016
DOI: 10.1063/1.4964280
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the tube diameter on the propagation of helium plasma plume via electric field measurement

Abstract: In this work, the dependence of the length of plasma plume, propagation velocity, electric field in the streamer head, and propagation mode transition on the tube diameter varied in the range of 0.07–4 mm is investigated for the first time. The atmospheric-pressure helium plasma plume, ignited by a positive pulsed direct current voltage with a pulse rising time of 60 ns, is confined inside a long glass tube. First, the decreased tube diameter results in the reduction of the length of plasma plume but the growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 32 publications
13
39
0
Order By: Relevance
“…They observed that the streamer velocity increases first and then decreases after reaching a peak at the tube diameter of 200 µm . In our previous work, for a He streamer propagating inside a tube, as the tube diameter decreases from 4 to 0.6 mm, the streamer velocity increases first and then decreases after reaching a peak at the tube diameter of 1 mm . These results are similar to our case.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…They observed that the streamer velocity increases first and then decreases after reaching a peak at the tube diameter of 200 µm . In our previous work, for a He streamer propagating inside a tube, as the tube diameter decreases from 4 to 0.6 mm, the streamer velocity increases first and then decreases after reaching a peak at the tube diameter of 1 mm . These results are similar to our case.…”
Section: Discussionsupporting
confidence: 91%
“…This also agrees well with the observation of the corona‐like air plasma for smaller capillaries in Figure . Similar behavior has been observed in our previous work, where the electric field strength in the head of the ionization front increases from 9 to 20 kV cm −1 for the tube diameter decreasing from 4 to 0.6 mm. The electric field in front of the ionization wave is composed of the external electric field and the local electric field induced by the charges.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We were able to point in this way that, for constant flow rate conditions and fixed electrode arrangement, the length of the outside jet depends on the frequency and amplitude of the driving high voltage pulses ( Figure 6). Supplementary, it has been demonstrated in a number of recent studies, that this characteristic dimension of the outside plasma jets in helium is also influenced by the electrodes dimensions and constructive details [40,41], gas flow rate [38,[42][43][44], dielectric tube diameter [45][46][47].…”
Section: Plasma Source Quasi-stationary Working Regimementioning
confidence: 99%